(6i+5)-(-10i-5)=0

Simple and best practice solution for (6i+5)-(-10i-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6i+5)-(-10i-5)=0 equation:


Simplifying
(6i + 5) + -1(-10i + -5) = 0

Reorder the terms:
(5 + 6i) + -1(-10i + -5) = 0

Remove parenthesis around (5 + 6i)
5 + 6i + -1(-10i + -5) = 0

Reorder the terms:
5 + 6i + -1(-5 + -10i) = 0
5 + 6i + (-5 * -1 + -10i * -1) = 0
5 + 6i + (5 + 10i) = 0

Reorder the terms:
5 + 5 + 6i + 10i = 0

Combine like terms: 5 + 5 = 10
10 + 6i + 10i = 0

Combine like terms: 6i + 10i = 16i
10 + 16i = 0

Solving
10 + 16i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 16i = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 16i = 0 + -10
16i = 0 + -10

Combine like terms: 0 + -10 = -10
16i = -10

Divide each side by '16'.
i = -0.625

Simplifying
i = -0.625

See similar equations:

| 4(3x-3)-2=4(x-4)+42 | | 3y-6y+2=8y+6-5 | | 3x+4/2=5/6 | | 8x^3-120=0 | | -8(3x+9)=15-7x | | 14x+8y=135 | | 15-3y=2y+6 | | 6x-3x+x-3+5x= | | -[9z-(17z+1)]=1+(7z+5) | | 8+7k=3k | | 3(8x+3)-2=22x+15 | | -32y+7=-18 | | (2xy-(3(x^2)))dx+((x^2)+y)dy=0 | | 5+7y-21y= | | 15p+7=qforp | | 9+6(6x-7)=-8-6(6x+4) | | 9x+7y=229 | | 5x^2+4x+5=5 | | 0.19x+0.7(x-4)=.01(2x-1) | | 5x^2+4c+5=5 | | 13-14= | | 33y^10+18y^6=0 | | -18-(-4)= | | -4-7s=5s+8 | | 65y^10+30y^7=0 | | 5x^2+23x-38=4 | | -8-(-1+6)= | | 9=A+b-c | | 2y+5=4y | | 7k+NJ=Jr+4m+3form | | y^2+12x=2y-13 | | 4(2x+5)=13x+17-5x+3 |

Equations solver categories